Lipofuscin accumulation and autophagy in glaucomatous human lamina cribrosa cells - McElnea, Elizabeth M (BMC Ophthalmol, 2014)
BACKGROUND: Disease associated alterations in the phenotype of lamina cribrosa (LC) cells are implicated in changes occurring at the optic nerve head (ONH) in glaucoma. Lipofuscin, the formation of which is driven by reactive oxygen species (ROS), is an intralysosomal, non-degradable, auto-fluorescent macromolecule which accumulates with age and can affect autophagy - the lysosomal degradation of a cell’s constituents. We aimed to compare the content of lipofuscin-like material and markers of autophagy in LC cells from normal and glaucoma donor eyes. METHODS: The number and size of peri-nuclear lysosomes were examined by transmission electron microscopy (TEM). Cellular auto-fluorescence was quantified by flow cytometry. Cathepsin K mRNA levels were assessed by PCR. Autophagy protein 5 (Atg5) mRNA and protein levels were analysed by PCR and Western blot. Protein levels of subunits of the microtubule associated proteins (MAP) 1A and 1B, light chain 3 (LC3) I and II were analysed by Western blot. Immunohistochemical staining of LC3-II in ONH sections from normal and glaucomatous donor eyes was performed. RESULTS: A significant increase in the number of peri-nuclear lysosomes [4.1 × 10,000 per high power field (h.p.f.) ± 1.9 vs. 2.0 × 10,000 per h.p.f. ± 1.3, p = 0.002, n = 3] and whole cell auto-fluorescence (83.62 ± 45.1 v 41.01 ± 3.9, p = 0.02, n = 3) was found in glaucomatous LC cells relative to normal LC cells. Glaucomatous LC cells possessed significantly higher levels of Cathepsin K mRNA and Atg5 mRNA and protein. Enhanced levels of LC3-II were found in both LC cells and optic nerve head sections from glaucoma donors. CONCLUSIONS: Increased lipofuscin formation is characteristic of LC cells from donors with glaucoma. This finding confirms the importance of oxidative stress in glaucoma pathogenesis. Intracellular lipofuscin accumulation may have important effects on autophagy the modification of which could form the basis for future novel glaucoma treatments.